Rickettsia conorii infection with fatal complication - Sanjoli Chugh,; Priyanka Kumari,; Shriya Goel,; Manisha Biswal,; Inderpaul Singh Sehgal,; Aravind Sekar, (Autopsy and Case Reports, 2022)
Rickettsial diseases (RD) are a group of endotheliotropic infectious diseases caused by different species of genera Rickettsia. RD are not an uncommon disease and may be misdiagnosed during the evaluation of acute febrile illness due to a lack of reliable serological marker and diagnostic culture methods. Clinical manifestation of RD varies from febrile illness with rashes and myalgia to fatal complications such as shock and respiratory failure. We describe a case of a young male who presented initially with acute febrile illness, followed by shock and respiratory failure, and unfortunately succumbed to death. A post-mortem examination showed histological features of endotheliotropic infection, such as interstitial / perivascular edema in various organs and noncardiogenic pulmonary edema (suggesting increased vascular permeability) and evidence of vasculitis in the lung, liver, and intestines. Molecular studies performed from lung, liver, and kidney tissue confirm the diagnosis of spotted fever group rickettsial disease due to Rickettsia conorii.